The Influence of The Principal's Leadership Agility, Teacher Competence and Work Environment in Readiness F for Change Through Employee Engagement Mediation The Don Bosco School Panca Dharma Foundation Jakarta - Lucia Sapto Wendah Wisanti; Kabul Wahyu Utomo; Janita Sembiring Meliala (Dinasti Publisher, 2025)
Changes in the Minister of Education have directly led to shifts in the national curriculum. The implementation of the new curriculum began gradually in 2023, requiring teachers to be ready to adapt. However, certain conditions indicate that this readiness is not yet fully evident. This study aims to examine the effect of principal leadership agility, teacher competence, and work environment on readiness for change, mediated by employee engagement at Don Bosco School, Panca Dharma Foundation, Jakarta. A quantitative associative method was used, with data collected through questionnaires from 181 teachers. Hypothesis testing was conducted using SEM-PLS (Partial Least Square) 3.0, with hypothesis acceptance based on t-statistics compared to the t-table value of 1.645 at a 0.05 significance level (one-tailed). Findings reveal that principal leadership agility, teacher competence, and work environment influence readiness for change by 60.10%, while 39.9% is influenced by other variables. These factors also affect employee engagement by 71.40%, with 28.6% attributed to other factors. Recommendations include encouraging principals to strengthen leadership skills and engage staff in strategic decision-making. School management is advised to maintain a supportive work environment to enhance teacher involvement and adaptability.